(3GdOQ GdefXhe aj HjGf MUQ GdYdhes - (3CMeO Hf YeQ Hf gdGd CHh GdYHGS TgGH GdOjf GdQHYj, GdQHYjs
(3ChdgG (B:s
(3CeG HYO , adeG cGf CYdG eG JSeh Edjg CYfGb Gdgee UfaJ gPg GdQSGdI GdhLjR ai HjGf MUQ GdYdhe s
(3BNQgG (B:s
(3hbGdgG eMeO Udi Gddg Ydjg hSde Mjf bGdhG (B( (3Ef GdfGS bO LeYhG dce aGMThge aRGOhge EjeGfG , hbGdhG (B: (3MSHfG Gddg hfYe Gdhcjd s
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B187s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B84 s
Keywords: (3GdeYGQa GdYGeIs